Deciphering the mutational signature of congenital limb malformations - Liying Sun; Yingzhao Huang; Sen Zhao; Junhui Zhao; Zihui Yan; Yang Guo; Mao Lin; Wenyao Zhong; Yuehan Yin; Zefu Chen; Nan Zhang; Yuanqiang Zhang; et al. (Elsevier, 2021)
Congenital limb malformations (CLMs) affect 1 in 500 live births. However, the value of exome sequencing (ES) for CLM is lacking. The purpose of this study was to decipher the mutational signature of CLM on an exome level. We enrolled a cohort of 66 unrelated probands (including 47 families) with CLM requiring surgical correction. ES was performed for all patients and available parental samples. A definite molecular diagnosis was achieved in 21 out of 66 (32%) patients. We identified 19 pathogenic or likely pathogenic single-nucleotide variants and three copy number variants, of which 11 variants were novel. We identified four variants of uncertain significance. Additionally, we identified RPL9 and UBA2 as novel candidate genes for CLM. By comparing the detailed phenotypic features, we expand the phenotypic spectrum of diastrophic dysplasia and chromosome 6q terminal deletion syndrome. We also found that the diagnostic rate was significantly higher in patients with a family history of CLM (p = 0.012) or more than one limb affected (p = 0.034). Our study expands our understanding of the mutational and phenotypic spectrum of CLM and provides novel insights into the genetic basis of these syndromes.